In vitro Antimicrobial Activity of Camellia sinensis and Myristica fragrans Against Staphylococcus aureus Pseudomonas aeruginosa Candida albicans - Kulandhaivel, M (International Journal of Pharmaceutical & Biological Archive, 2012)
In vitro Antimicrobial Activity of Camellia sinensis and Myristica fragrans Against Staphylococcus aureus Pseudomonas aeruginosa Candida albicans